Case Report: Cerebral lipiodol embolism in the Guangxi Zhuang autonomous region, Southwest China - Le, Wen-Jun; Huang, Jin-Yu; Mao, Zhen-Fang; Mo, Zhen-Hua; Chen, Hong-Qiao; Wei, Wu-Xiao (Frontiers in Medicine, 2025)
PurposeThis study aims to provide insights into the rare occurrence of cerebral lipiodol embolism following transcatheter arterial chemoembolization (TACE) in treating hepatocellular carcinoma (HCC). By analyzing a specific case, this research seeks to enhance clinical understanding of the pathogenesis, manifestations, and management strategies for this complication, ultimately improving patient outcomes.BackgroundCerebral lipiodol embolism is an infrequent yet severe complication of TACE, a standard treatment for unresectable HCC. The embolism occurs when iodized oil, used during the procedure, inadvertently enters the cerebral circulation, often due to arteriovenous shunts associated with liver tumors. Despite TACE’s widespread use, awareness and understanding of this rare complication remain limited, necessitating further investigation to mitigate risks and improve patient safety.Case presentationA 64-year-old man with multiple HCCs and portal vein invasion underwent TACE involving iodized oil and chemotherapy agents. Post-procedure, the patient exhibited neurological deficits, including decreased consciousness and right-sided weakness. Imaging confirmed cerebral lipiodol embolism. Despite gradual neurological improvement, the patient continued to experience significant right-sided weakness, highlighting the long-term impact of this complication.ConclusionCerebral lipiodol embolism, though rare, poses significant risks during TACE. Early detection through careful imaging and precautionary measures, such as managing Lipiodol injection volumes and speeds, is crucial. Enhanced clinical awareness and intervention strategies can prevent lipiodol from entering the systemic circulation, reducing the incidence of this severe complication.